Low-rolling-resistance rubber nano composite material, preparation method and application thereof, and vulcanized rubber prepared from low-rolling-resistance rubber nano composite material

By modifying the modified crude carbon dot and white carbon black, low-roll resistance rubber nanocomposite material is prepared for tire tread glue, which solves the problem of high rolling resistance of existing tires and achieves lower rolling resistance and higher joints Oil effect.

CN119307019AActive Publication Date: 2025-01-14BEIJING UNIV OF CHEM TECH
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202310852584.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-12
Publication Date
2025-01-14
Estimated Expiration
2043-07-12

AI Technical Summary

Technical Problem

The rolling resistance coefficient of existing tires is relatively high, which affects automobile fuel consumption, and the existing technology is difficult to effectively reduce the rolling resistance of tires.

Method used

By modifying and modifying the crude carbon dots and white carbon black, a low-roll resistance rubber nanocomposite was prepared, and vulcanized after mixing and vulcanizing to obtain vulcanized rubber for tread glue, which reduces the rolling resistance coefficient of the tire.

Benefits of technology

It improves the tensile and tear performance of rubber nanocomposites, significantly reduces the rolling resistance coefficient of the tire, has great fuel saving advantages, and simplifies the processing technology, which is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004334772040000021
    Figure BDA0004334772040000021
  • Figure BDA0004334772040000022
    Figure BDA0004334772040000022
  • Figure BDA0004334772040000131
    Figure BDA0004334772040000131
Patent Text Reader

Abstract

The invention relates to a rubber material, and further relates to a low-rolling-resistance rubber nano composite material, a preparation method and application thereof, and vulcanized rubber prepared from the low-rolling-resistance rubber nano composite material. According to the invention, the white carbon black and the rubber material are modified by using the coarse carbon dots, and the low-rolling-resistance rubber nano composite material is obtained after mixing; the tensile property and the tearing property of the low-rolling-resistance rubber nano composite material are improved. Vulcanized rubber is obtained by vulcanizing the low-rolling-resistance rubber nano composite material, the rolling resistance coefficient of the vulcanized rubber serving as tread rubber is small, and a tire product prepared from the vulcanized rubber has lower rolling resistance and has a great oil-saving advantage when applied to green tires.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a rubber material, and more particularly to a low rolling resistance rubber nanocomposite material and a preparation method, application and prepared vulcanized rubber thereof. Background Art

[0002] With the rapid development of the automobile industry, cars have become an indispensable means of transportation in people's lives. The development of the automobile industry has also promoted the continuous innovation and progress of the tire industry. With the increasingly stringent environmental regulations and the increasing shortage of oil resources, how to reduce automobile fuel consumption has become the focus of the automobile industry and consumers.

[0003] Wind resistance, tire rolling resistance and mechanical resistance are the main factors affecting automobile fuel consumption, of which tire rolling resistance accounts for 20% to 30%, and the energy consumption caused by tire rolling resistance accounts for 15% of fuel consumption. This means that reducing rolling resistance by 30% can save about 4.5% of fuel. The rolling resistance coefficient of existing tires is usually higher than 0.18.

[0004] Among the factors that affect the rolling resistance performance of tires, the rubber compound formula accounts for about 50%, so the rolling resistance of tires can be reduced by adjusting the tread rubber formula. How to reduce the rolling resistance coefficient of tires by changing the rubber compound formula is a technical problem urgently needed in the field of rubber technology. Summary of the invention

[0005] In order to solve the above technical problems existing in the prior art, the present invention utilizes coarse carbon dots to modify white carbon black and rubber materials, and obtains a rubber nanocomposite material after mixing; the tensile and tear properties of the rubber nanocomposite material are improved; the rubber nanocomposite material is further vulcanized to obtain a vulcanized rubber, and the vulcanized rubber is used as a tread rubber of a tire, and its rolling resistance coefficient is small. The tire product prepared by the vulcanized rubber has lower rolling resistance, and has a greater fuel-saving advantage when used in green tires.

[0006] One of the purposes of the present invention is to provide a low rolling resistance rubber nanocomposite material.

[0007] The low rolling resistance rubber nanocomposite material is prepared by mixing raw materials including the following components:

[0008] Each component is measured by weight:

[0009]

[0010] The crude carbon dots are prepared from organic acid and fatty amine.

[0011] The weight parts of each component are preferably:

[0012]

[0013] More preferably, based on 100 parts by weight of rubber, the amount of the coarse carbon dots is 5-15 parts; further preferably, based on 100 parts by weight of rubber, the amount of the coarse carbon dots is 5-10 parts.

[0014] The rubber is a bio-based rubber or / and a petroleum-based rubber; preferably one or more of natural rubber, epoxy natural rubber, itaconate rubber, styrene-butadiene rubber, nitrile rubber and butadiene rubber; more preferably one or more of natural rubber, epoxy natural rubber and itaconate rubber. The itaconate rubber is described in patent CN104945817A.

[0015] The organic acid is at least one of citric acid, malic acid, oxalic acid, lactic acid, acetic acid and tartaric acid; preferably citric acid and / or malic acid; or / and,

[0016] The fatty amine is at least one of ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine and polyethylenepolyamines; preferably diethylenetriamine and / or triethylenetetramine.

[0017] The antioxidant may be one or more of the antioxidants commonly used in the prior art, for example, antioxidant 4020 and / or antioxidant RD. When antioxidant 4020 and antioxidant RD are used as antioxidants, the weight ratio of the two may be 1:1.

[0018] The accelerator may be one or more of the accelerators commonly used in the prior art, for example, accelerator CZ and / or accelerator DM. When accelerator CZ and accelerator DM are used as accelerators, the weight ratio of the two may be 1:1.

[0019] The white carbon black may be one or more of the white carbon blacks commonly used in the prior art, for example, white carbon black VN3.

[0020] The silane coupling agent may be one or more of the silane coupling agents commonly used in the prior art, for example, silane coupling agent Si69.

[0021] Experiments have found that there is a close relationship between the relative amount of coarse carbon dots and the rolling resistance coefficient of the prepared rubber nanocomposite. In order to obtain a rubber nanocomposite with a lower rolling resistance coefficient, the present invention limits the amount of coarse carbon dots to: the weight ratio of coarse carbon dots to white carbon black is 1:3 to 30; for example: 1:3 to 7, 1:7 to 10, 1:10 to 25, 1:25 to 30. In order to further reduce the rolling resistance coefficient of the prepared rubber nanocomposite, the weight ratio of the coarse carbon dots to white carbon black is preferably 1:3 to 7.

[0022] The change in the molar ratio of the organic acid and the fatty amine will affect the modification performance of the prepared crude carbon dots on white carbon black and rubber, and will affect the rolling resistance coefficient of the prepared rubber nanocomposite. In order to obtain a rubber nanocomposite with a lower rolling resistance coefficient, the molar ratio of the organic acid and the fatty amine used to prepare the crude carbon dots is 1:1-5; for example: 1:1-2, 1:2-3, 1:3-5. In order to obtain a rubber nanocomposite with an even lower rolling resistance coefficient, the molar ratio of the organic acid and the fatty amine is preferably 1:2-3.

[0023] The crude carbon dots are a viscous liquid with poor fluidity and emit light under a 365nm ultraviolet lamp. The luminescent color of the crude carbon dots under a 365nm ultraviolet lamp is determined by the raw materials; the color of the light is different depending on the raw materials, for example, in a citric acid and diethylenetriamine system, it is light blue. The crude carbon dots are prepared by a microwave method or a hydrothermal method. When the microwave method is used to prepare the crude carbon dots, the microwave reaction time is determined by the amount of the raw materials used, and the microwave reaction time is usually 5 to 30 minutes, preferably 6 to 10 minutes.

[0024] In order to improve the dispersibility of white carbon black in the rubber nanocomposite material and further improve the comprehensive performance of the rubber nanocomposite material, maleic anhydride adducted polybutadiene can be added to the raw material formula; the weight proportion of maleic anhydride adducted polybutadiene is 1 to 10 parts; for example, 1 to 2 parts, 2 to 5 parts, 5 to 10 parts; preferably 5 to 10 parts.

[0025] The second object of the present invention is to provide a method for preparing a low rolling resistance rubber nanocomposite material.

[0026] The method for preparing the low rolling resistance rubber nanocomposite material comprises mixing the crude carbon dots with deionized water and then kneading the mixture with the remaining components in the amounts to obtain the rubber nanocomposite material. That is, taking the crude carbon dots according to weight, mixing the crude carbon dots with deionized water to obtain a crude carbon dots aqueous solution, and then kneading the crude carbon dots aqueous solution with the remaining components in the amounts to obtain the rubber nanocomposite material. The amount of deionized water used is sufficient to dissolve the crude carbon dots, and the amount does not affect the performance of the prepared rubber nanocomposite material. Specifically, the crude carbon dots are mixed with deionized water to obtain a crude carbon dots aqueous solution with a solid content of 50±20wt%.

[0027] The third object of the present invention is to provide a vulcanized rubber. The vulcanized rubber is made by compression vulcanizing the low rolling resistance rubber nanocomposite material at 120-180°C.

[0028] The fourth object of the present invention is to provide an application of a low rolling resistance rubber nanocomposite material and an application of the low rolling resistance rubber nanocomposite material in tires.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] Compared with existing rubber materials, the low rolling resistance rubber nanocomposite provided by the present invention has improved tensile and tearing properties and reduced rolling resistance coefficient. When used in tires, it can improve the anti-skid property of tires, reduce the rolling resistance of tires, and make tires have lower rolling resistance. It has a great fuel saving advantage when used in green tires. Effectively improving the rolling resistance of rubber is of great significance to the processing and manufacturing of rubber, reducing costs, saving fuel and alleviating environmental pressure.

[0031] The present invention does not need to pre-mix the crude carbon dots with white carbon black, but mixes the crude carbon dots, white carbon black and other raw materials simultaneously; water can be removed during the mixing process, and no drying step is required; the processing technology is simple and suitable for industrial preparation.

[0032] The rubber used in the present invention is a bulk industrial rubber, which has a wide range of applications in industrial production. The carbon dots prepared by microwave and hydrothermal methods are environmentally friendly and have low energy consumption, and the process is simple and suitable for industrial production. DETAILED DESCRIPTION

[0033] The present invention is described in detail below in conjunction with the embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.

[0034] DSC: The SATRE System DSC tester produced by METTLER TOLEDO of Switzerland was used. The test conditions were as follows: the temperature was first raised from room temperature to 100°C at a heating rate of 20°C / min, kept at 100°C for 3 minutes, then lowered from 100°C to ~80°C at a cooling rate of 20°C / min, and then raised to 100°C at a heating rate of 10°C / min. The heat change during the second heating process was recorded. The glass transition temperature is the midpoint of the hot melt transition in the curve.

[0035] RPA: Rubber Processing Analysis tests were performed using an Alpha RPA 2000 rheometer at 60 °C and 1 Hz on the uncured compounds and nanocomposites.

[0036] The itaconate rubber in the embodiment is prepared according to Example 3 of patent CN104945817B; the other raw materials used are commercially available products.

[0037] Example 1

[0038] 1 mol of citric acid and 1 mol of diethylenetriamine were prepared into crude carbon dots by microwave method. The specific operation is as follows: add an appropriate amount of deionized water (the amount of water is not critical and will be removed in subsequent treatment) to dissolve citric acid; slowly drip diethylenetriamine into the citric acid aqueous solution, and then stir magnetically for about ten minutes to obtain a mixed solution. The mixed solution was placed in a microwave oven and reacted until the system was a viscous liquid with extremely poor fluidity and emitted light under a 365nm ultraviolet lamp. The obtained viscous liquid with extremely poor fluidity was the crude carbon dots.

[0039] 10 parts by weight of crude carbon dots were weighed, and 10 parts by weight of deionized water were added, and magnetic stirring was performed until a homogeneous phase was obtained to obtain a crude carbon dot aqueous solution with a solid content of 50 wt%.

[0040] 100 parts by weight of natural rubber, 5 parts by weight of zinc oxide, 2 parts by weight of stearic acid, 1 part by weight of antioxidant 4020, 1 part by weight of antioxidant RD, 1 part by weight of accelerator CZ, 1 part by weight of accelerator DM, 1.5 parts by weight of sulfur, 50 parts by weight of white carbon black VN3, 5 parts by weight of silane coupling agent Si69, and 10 parts by weight of the above-mentioned crude carbon dot aqueous solution (that is, the amount of crude carbon dots is 5 parts) are first mixed and dehydrated at a speed of 70 rpm in an internal mixer, and then mixed evenly on a double-roll open mill to obtain a rubber compound, the rubber compound is molded and vulcanized at 145°C to prepare a natural rubber vulcanizate, and then the performance of the natural rubber vulcanizate is tested.

[0041] Example 2

[0042] 1 mole of citric acid and 2 moles of diethylenetriamine were used to prepare crude carbon dots by microwave method. The specific operation was the same as that in Example 1. 10 parts by weight of crude carbon dots were weighed, 10 parts by weight of deionized water were added, and magnetic stirring was performed until homogeneous to obtain a crude carbon dot aqueous solution with a solid content of 50 wt%.

[0043] 100 parts by weight of natural rubber, 5 parts by weight of zinc oxide, 2 parts by weight of stearic acid, 1 part by weight of antioxidant 4020, 1 part by weight of antioxidant RD, 1 part by weight of accelerator CZ, 1 part by weight of accelerator DM, 1.5 parts by weight of sulfur, 50 parts by weight of white carbon black VN3, 5 parts by weight of silane coupling agent Si69, and 10 parts by weight of the above crude carbon dot aqueous solution are first mixed and dehydrated in an internal mixer at a speed of 70 rpm, and then mixed evenly on a double-roll open mill to obtain a rubber compound, the rubber compound is molded and vulcanized at 145°C to prepare a natural rubber vulcanizate, and then the performance of the natural rubber vulcanizate is tested.

[0044] Example 3

[0045] 1 mole of citric acid and 3 moles of diethylenetriamine were used to prepare crude carbon dots by microwave method. The specific operation was the same as that in Example 1. 10 parts by weight of crude carbon dots were weighed, 10 parts by weight of deionized water were added, and magnetic stirring was performed until homogeneous to obtain a crude carbon dot aqueous solution with a solid content of 50 wt%.

[0046] 100 parts by weight of natural rubber, 5 parts by weight of zinc oxide, 2 parts by weight of stearic acid, 1 part by weight of antioxidant 4020, 1 part by weight of antioxidant RD, 1 part by weight of accelerator CZ, 1 part by weight of accelerator DM, 1.5 parts by weight of sulfur, 50 parts by weight of white carbon black VN3, 5 parts by weight of silane coupling agent Si69, and 10 parts by weight of the above crude carbon dot aqueous solution are first mixed and dehydrated in an internal mixer at a speed of 70 rpm, and then mixed evenly on a double-roll open mill to obtain a rubber compound, the rubber compound is molded and vulcanized at 145°C to prepare a natural rubber vulcanizate, and then the performance of the natural rubber vulcanizate is tested.

[0047] Example 4

[0048] 1 mol of citric acid and 3 mol of diethylenetriamine were used to prepare crude carbon dots by microwave method. The specific operation was the same as that in Example 1. 5 wt. parts of crude carbon dots were weighed, 5 wt. parts of deionized water were added, and magnetic stirring was performed until homogeneous to obtain a crude carbon dot aqueous solution with a solid content of 50 wt.%.

[0049] 100 parts by weight of natural rubber, 5 parts by weight of zinc oxide, 2 parts by weight of stearic acid, 1 part by weight of antioxidant 4020, 1 part by weight of antioxidant RD, 1 part by weight of accelerator CZ, 1 part by weight of accelerator DM, 1.5 parts by weight of sulfur, 50 parts by weight of white carbon black VN3, 5 parts by weight of silane coupling agent Si69, and 14 parts by weight of the above crude carbon dot aqueous solution are first mixed and dehydrated in an internal mixer at a speed of 70 rpm, and then mixed evenly on a double-roll open mill to obtain a rubber compound, the rubber compound is molded and vulcanized at 145°C to prepare a natural rubber vulcanizate, and then the performance of the natural rubber vulcanizate is tested.

[0050] Example 5

[0051] 1 mol of citric acid and 3 mol of diethylenetriamine were used to prepare crude carbon dots by microwave method. The specific operation was the same as that in Example 1. 1 wt. part of crude carbon dots was weighed, 1 wt. part of deionized water was added, and magnetic stirring was performed until homogeneous to obtain a crude carbon dot aqueous solution with a solid content of 50 wt.%.

[0052] 100 parts by weight of natural rubber, 5 parts by weight of zinc oxide, 2 parts by weight of stearic acid, 1 part by weight of antioxidant 4020, 1 part by weight of antioxidant RD, 1 part by weight of accelerator CZ, 1 part by weight of accelerator DM, 1.5 parts by weight of sulfur, 50 parts by weight of white carbon black VN3, 5 parts by weight of silane coupling agent Si69, and 4 parts by weight of the above-mentioned crude carbon dot aqueous solution are first mixed and dehydrated in an internal mixer at a speed of 70 rpm, and then mixed evenly on a double-roll open mill to obtain a rubber compound, the rubber compound is molded and vulcanized at 145°C to prepare a natural rubber vulcanizate, and then the performance of the natural rubber vulcanizate is tested.

[0053] Example 6

[0054] 1 mol of citric acid and 3 mol of diethylenetriamine were used to prepare crude carbon dots by microwave method. The specific operation was the same as that in Example 1. 5 wt. parts of crude carbon dots were weighed, 5 wt. parts of deionized water were added, and magnetic stirring was performed until homogeneous to obtain a crude carbon dot aqueous solution with a solid content of 50 wt.%.

[0055] 100 parts by weight of natural rubber, 5 parts by weight of zinc oxide, 2 parts by weight of stearic acid, 1 part by weight of antioxidant 4020, 1 part by weight of antioxidant RD, 1 part by weight of accelerator CZ, 1 part by weight of accelerator DM, 1.5 parts by weight of sulfur, 30 parts by weight of white carbon black VN3, 3 parts by weight of Si69, and 4 parts by weight of the above-mentioned crude carbon dot aqueous solution are first mixed and removed from water in an internal mixer at a rotation speed of 70 rpm, and then mixed evenly on a double-roll open mill to obtain a rubber compound, the rubber compound is molded and vulcanized at 145°C to prepare a natural rubber vulcanizate, and then its performance is tested.

[0056] Example 7

[0057] 1 mol of citric acid and 3 mol of diethylenetriamine were used to prepare crude carbon dots by microwave method. The specific operation was the same as that in Example 1. 5 wt. parts of crude carbon dots were weighed, 5 wt. parts of deionized water were added, and magnetic stirring was performed until homogeneous to obtain a crude carbon dot aqueous solution with a solid content of 50 wt.%.

[0058] 100 parts by weight of natural rubber, 5 parts by weight of zinc oxide, 2 parts by weight of stearic acid, 1 part by weight of antioxidant 4020, 1 part by weight of antioxidant RD, 1 part by weight of accelerator CZ, 1 part by weight of accelerator DM, 1.5 parts by weight of sulfur, 60 parts by weight of white carbon black VN3, 6 parts by weight of Si69, and 4 parts by weight of the above-mentioned crude carbon dot aqueous solution are first mixed and removed from water in an internal mixer at a speed of 70 rpm, and then mixed evenly on a double-roll open mill to obtain a rubber compound, the rubber compound is molded and vulcanized at 145°C to prepare a natural rubber vulcanizate, and then its performance is tested.

[0059] Example 8

[0060] 1 mole of citric acid and 3 moles of diethylenetriamine were used to prepare crude carbon dots by microwave method. The specific operation was the same as that in Example 1. 10 parts by weight of crude carbon dots were weighed, 10 parts by weight of deionized water were added, and magnetic stirring was performed until homogeneous to obtain a crude carbon dot aqueous solution with a solid content of 50 wt%.

[0061] 100 parts by weight of itaconate rubber, 5 parts by weight of zinc oxide, 2 parts by weight of stearic acid, 1 part by weight of antioxidant 4020, 1 part by weight of antioxidant RD, 1 part by weight of accelerator CZ, 1 part by weight of accelerator DM, 1.5 parts by weight of sulfur, 50 parts by weight of white carbon black VN3, 5 parts by weight of silane coupling agent Si69, and 10 parts by weight of the above crude carbon dot aqueous solution are first mixed and dehydrated in an internal mixer at a speed of 70 rpm, and then mixed evenly on a double-roll open mill to obtain a rubber compound, the rubber compound is molded and vulcanized at 150°C to prepare a natural rubber vulcanizate, and then the performance of the natural rubber vulcanizate is tested.

[0062] Example 9

[0063] 1 mole of citric acid and 3 moles of diethylenetriamine were used to prepare crude carbon dots by microwave method. The specific operation was the same as that in Example 1. 10 parts by weight of crude carbon dots were weighed, 10 parts by weight of deionized water were added, and magnetic stirring was performed until homogeneous to obtain a crude carbon dot aqueous solution with a solid content of 50 wt%.

[0064] 100 parts by weight of epoxy natural rubber, 5 parts by weight of zinc oxide, 2 parts by weight of stearic acid, 1 part by weight of antioxidant 4020, 1 part by weight of antioxidant RD, 1 part by weight of accelerator CZ, 1 part by weight of accelerator DM, 1.5 parts by weight of sulfur, 50 parts by weight of white carbon black VN3, 5 parts by weight of silane coupling agent Si69, and 10 parts by weight of the above crude carbon dot aqueous solution are first mixed and dehydrated in an internal mixer at a speed of 70 rpm, and then mixed evenly on a double-roll open mill to obtain a rubber compound, the rubber compound is molded and vulcanized at 150°C to prepare a natural rubber vulcanizate, and then the performance of the natural rubber vulcanizate is tested.

[0065] Example 10

[0066] 1 mole of citric acid and 3 moles of diethylenetriamine were used to prepare crude carbon dots by microwave method. The specific operation was the same as that in Example 1. 10 parts by weight of crude carbon dots were weighed, 10 parts by weight of deionized water were added, and magnetic stirring was performed until homogeneous to obtain a crude carbon dot aqueous solution with a solid content of 50 wt%.

[0067] 100 parts by weight of epoxy natural rubber, 5 parts by weight of zinc oxide, 2 parts by weight of stearic acid, 1 part by weight of antioxidant 4020, 1 part by weight of antioxidant RD, 1 part by weight of accelerator CZ, 1 part by weight of accelerator DM, 1.5 parts by weight of sulfur, 50 parts by weight of white carbon black VN3, 5 parts by weight of silane coupling agent Si69, and 30 parts by weight of the above crude carbon dot aqueous solution are first mixed and dehydrated in an internal mixer at a speed of 70 rpm, and then mixed evenly on a double-roll open mill to obtain a rubber compound, the rubber compound is molded and vulcanized at 150°C to prepare a natural rubber vulcanizate, and then its performance is tested.

[0068] Embodiment 11

[0069] 1 mole of citric acid and 3 moles of diethylenetriamine were used to prepare crude carbon dots by microwave method. The specific operation was the same as that in Example 1. 10 parts by weight of crude carbon dots were weighed, 10 parts by weight of deionized water were added, and magnetic stirring was performed until homogeneous to obtain a crude carbon dot aqueous solution with a solid content of 50 wt%.

[0070] 100 parts by weight of epoxy natural rubber, 1 part by weight of maleic anhydride-adducted polybutadiene, 5 parts by weight of zinc oxide, 2 parts by weight of stearic acid, 1 part by weight of antioxidant 4020, 1 part by weight of antioxidant RD, 1 part by weight of accelerator CZ, 1 part by weight of accelerator DM, 1.5 parts by weight of sulfur, 50 parts by weight of white carbon black VN3, 5 parts by weight of silane coupling agent Si69, and 10 parts by weight of the above-mentioned crude carbon dot aqueous solution are first mixed and dehydrated in an internal mixer at a speed of 70 rpm, and then mixed evenly on a double-roll open mill to obtain a rubber compound, the rubber compound is molded and vulcanized at 150°C to prepare a natural rubber vulcanizate, and then the performance of the natural rubber vulcanizate is tested.

[0071] Example 12

[0072] 1 mole of citric acid and 3 moles of diethylenetriamine were used to prepare crude carbon dots by microwave method. The specific operation was the same as that in Example 1. 10 parts by weight of crude carbon dots were weighed, 10 parts by weight of deionized water were added, and magnetic stirring was performed until homogeneous to obtain a crude carbon dot aqueous solution with a solid content of 50 wt%.

[0073] 100 parts by weight of epoxy natural rubber, 2 parts by weight of maleic anhydride added polybutadiene, 5 parts by weight of zinc oxide, 2 parts by weight of stearic acid, 1 part by weight of antioxidant 4020, 1 part by weight of antioxidant RD, 1 part by weight of accelerator CZ, 1 part by weight of accelerator DM, 1.5 parts by weight of sulfur, 50 parts by weight of white carbon black VN3, 5 parts by weight of silane coupling agent Si69, and 10 parts by weight of the above crude carbon dot aqueous solution are first mixed and dehydrated in an internal mixer at a speed of 70 rpm, and then mixed evenly on a double-roll open mill to obtain a rubber compound, the rubber compound is molded and vulcanized at 150°C to prepare a natural rubber vulcanizate, and then the performance of the natural rubber vulcanizate is tested.

[0074] Example 13

[0075] 1 mole of citric acid and 3 moles of diethylenetriamine were used to prepare crude carbon dots by microwave method. The specific operation was the same as that in Example 1. 10 parts by weight of crude carbon dots were weighed, 10 parts by weight of deionized water were added, and magnetic stirring was performed until homogeneous to obtain a crude carbon dot aqueous solution with a solid content of 50 wt%.

[0076] 100 parts by weight of epoxy natural rubber, 5 parts by weight of maleic anhydride-adducted polybutadiene, 5 parts by weight of zinc oxide, 2 parts by weight of stearic acid, 1 part by weight of antioxidant 4020, 1 part by weight of antioxidant RD, 1 part by weight of accelerator CZ, 1 part by weight of accelerator DM, 1.5 parts by weight of sulfur, 50 parts by weight of white carbon black VN3, 5 parts by weight of silane coupling agent Si69, and 10 parts by weight of the above-mentioned crude carbon dot aqueous solution are first mixed and dehydrated in an internal mixer at a speed of 70 rpm, and then mixed evenly on a double-roll open mill to obtain a rubber compound, the rubber compound is molded and vulcanized at 150°C to prepare a natural rubber vulcanizate, and then the performance of the natural rubber vulcanizate is tested.

[0077] Embodiment 14

[0078] 1 mole of citric acid and 3 moles of diethylenetriamine were used to prepare crude carbon dots by microwave method. The specific operation was the same as that in Example 1. 10 parts by weight of crude carbon dots were weighed, 10 parts by weight of deionized water were added, and magnetic stirring was performed until homogeneous to obtain a crude carbon dot aqueous solution with a solid content of 50 wt%.

[0079] 100 parts by weight of epoxy natural rubber, 10 parts by weight of maleic anhydride-adducted polybutadiene, 5 parts by weight of zinc oxide, 2 parts by weight of stearic acid, 1 part by weight of antioxidant 4020, 1 part by weight of antioxidant RD, 1 part by weight of accelerator CZ, 1 part by weight of accelerator DM, 1.5 parts by weight of sulfur, 50 parts by weight of white carbon black VN3, 5 parts by weight of silane coupling agent Si69, and 10 parts by weight of the above-mentioned crude carbon dot aqueous solution are first mixed and dehydrated in an internal mixer at a speed of 70 rpm, and then mixed evenly on a double-roll open mill to obtain a rubber compound, the rubber compound is molded and vulcanized at 150°C to prepare a natural rubber vulcanizate, and then the performance of the natural rubber vulcanizate is tested.

[0080] Embodiment 15

[0081] 1 mole of citric acid and 3 moles of diethylenetriamine were used to prepare crude carbon dots by microwave method. The specific operation was the same as that in Example 1. 10 parts by weight of crude carbon dots were weighed, 10 parts by weight of deionized water were added, and magnetic stirring was performed until homogeneous to obtain a crude carbon dot aqueous solution with a solid content of 50 wt%.

[0082] 100 parts by weight of styrene-butadiene rubber, 5 parts by weight of zinc oxide, 2 parts by weight of stearic acid, 1 part by weight of antioxidant 4020, 1 part by weight of antioxidant RD, 1 part by weight of accelerator CZ, 1 part by weight of accelerator DM, 1.5 parts by weight of sulfur, 50 parts by weight of white carbon black VN3, 5 parts by weight of silane coupling agent Si69 and 0.5 parts by weight of crude carbon dots (i.e., 1 part by weight of crude carbon dots aqueous solution) are first mixed and dehydrated in an internal mixer at a speed of 70 rpm, and then mixed evenly on a double-roll open mill to obtain a rubber compound, the rubber compound is molded and vulcanized at 150°C to prepare a styrene-butadiene rubber vulcanizate, and then the performance of the rubber compound is tested.

[0083] Example 16

[0084] 1 mol of citric acid and 3 mol of diethylenetriamine were used to prepare crude carbon dots by microwave method. The specific operation was the same as that in Example 1. 5 wt. parts of crude carbon dots were weighed, 5 wt. parts of deionized water were added, and magnetic stirring was performed until homogeneous to obtain a crude carbon dot aqueous solution with a solid content of 50 wt.%.

[0085] 100 parts by weight of natural rubber, 5 parts by weight of zinc oxide, 2 parts by weight of stearic acid, 1 part by weight of antioxidant 4020, 1 part by weight of antioxidant RD, 1 part by weight of accelerator CZ, 1 part by weight of accelerator DM, 1.5 parts by weight of sulfur, 50 parts by weight of white carbon black VN3, 5 parts by weight of silane coupling agent Si69, and 2 parts by weight of the above-mentioned crude carbon dot aqueous solution are first mixed and removed from water in an internal mixer at a speed of 70 rpm, and then mixed evenly on a double-roll open mill to obtain a rubber compound, the rubber compound is molded and vulcanized at 145°C to prepare a natural rubber vulcanizate, and then the performance of the natural rubber vulcanizate is tested.

[0086] Embodiment 17

[0087] 1 mol of citric acid and 3 mol of diethylenetriamine were used to prepare crude carbon dots by microwave method. The specific operation was the same as that in Example 1. 5 wt. parts of crude carbon dots were weighed, 5 wt. parts of deionized water were added, and magnetic stirring was performed until homogeneous to obtain a crude carbon dot aqueous solution with a solid content of 50 wt.%.

[0088] 100 parts by weight of natural rubber, 5 parts by weight of zinc oxide, 2 parts by weight of stearic acid, 1 part by weight of antioxidant 4020, 1 part by weight of antioxidant RD, 1 part by weight of accelerator CZ, 1 part by weight of accelerator DM, 1.5 parts by weight of sulfur, 50 parts by weight of white carbon black VN3, 5 parts by weight of silane coupling agent Si69, and 30 parts by weight of the above crude carbon dot aqueous solution are first mixed and dehydrated in an internal mixer at a speed of 70 rpm, and then mixed evenly on a double-roll open mill to obtain a rubber compound, the rubber compound is molded and vulcanized at 145°C to prepare a natural rubber vulcanizate, and then the performance of the natural rubber vulcanizate is tested.

[0089] Embodiment 18

[0090] 1 mol of citric acid and 3 mol of diethylenetriamine were used to prepare crude carbon dots by microwave method. The specific operation was the same as that in Example 1. 5 wt. parts of crude carbon dots were weighed, 5 wt. parts of deionized water were added, and magnetic stirring was performed until homogeneous to obtain a crude carbon dot aqueous solution with a solid content of 50 wt.%.

[0091] 100 parts by weight of natural rubber, 5 parts by weight of zinc oxide, 2 parts by weight of stearic acid, 1 part by weight of antioxidant 4020, 1 part by weight of antioxidant RD, 1 part by weight of accelerator CZ, 1 part by weight of accelerator DM, 1.5 parts by weight of sulfur, 50 parts by weight of white carbon black VN3, 5 parts by weight of silane coupling agent Si69, and 60 parts by weight of the above crude carbon dot aqueous solution are first mixed and dehydrated in an internal mixer at a speed of 70 rpm, and then mixed evenly on a double-roll open mill to obtain a rubber compound, the rubber compound is molded and vulcanized at 145°C to prepare a natural rubber vulcanizate, and then the performance of the natural rubber vulcanizate is tested.

[0092] Comparative Example

[0093] 100 parts by weight of styrene-butadiene rubber, 5 parts by weight of zinc oxide, 2 parts by weight of stearic acid, 1 part by weight of antioxidant 4020, 1 part by weight of antioxidant RD, 1 part by weight of accelerator CZ, 1 part by weight of accelerator DM, 1.5 parts by weight of sulfur, 50 parts by weight of white carbon black VN3, and 5 parts by weight of silane coupling agent Si69 were first mixed in an internal mixer at a rotation speed of 70 rpm, and then mixed evenly on a double-roll open mill to obtain a rubber compound, the rubber compound was molded and vulcanized at 150°C to prepare a styrene-butadiene rubber vulcanizate, and then the performance of the rubber compound was tested.

[0094] Table 1. Performance test results of various comparative examples

[0095]

[0096] The above examples and comparative examples were tested according to the following standards: Tensile test: According to ASTM D412 (dumbbell specimen), tensile strength, tensile stress (300%), elongation at break (GB / T528-2009). The relationship between loss factor (tanδ) and strain was tested by rubber processing analyzer (RPA).

[0097] The loss factor (0.16) of Example 1 at a strain of 7% is not significantly reduced compared to that of the comparative example (0.18). The study found that in reducing the rolling resistance, the amino group (NH-) also participates in the formation of hydrogen bonds. When the molar ratio of citric acid to diethylenetriamine is 1:1, the amine content is relatively low, so the rolling resistance is not significantly reduced, which is reflected in the fact that the loss factor at a strain of 7% is not significantly reduced.

[0098] The loss factor (0.06) of Example 4 at a strain of 7% is significantly reduced compared to that of the comparative example (0.18). On the one hand, the coarse carbon dots added in Example 3 are composed of citric acid and diethylenetriamine in a molar ratio of 1:3, and the amine content is relatively high; on the other hand, the amount of coarse carbon dots added is relatively large, resulting in a high amine content; therefore, the rolling resistance is significantly reduced, which is reflected in the significant reduction in the loss factor at a strain of 7%.

[0099] The following conclusions can be drawn from the test: the tensile strength of the rubber prepared by adding coarse carbon dots to the rubber base material can reach about 30MPa, the elongation at break is 500-600%, and the loss factor at a strain of 7% is 0.09-0.16. The low loss factor of the rubber prepared by adding coarse carbon dots indicates that it has low rolling resistance as a tread rubber. In short, adding coarse carbon dots can effectively reduce the rolling resistance of rubber, which is of great significance to the processing and manufacturing of rubber, reducing costs, saving fuel and alleviating environmental pressure.

Claims

1. A low rolling resistance rubber nanocomposite material, characterized in that: The rubber nanocomposite material is prepared by mixing raw materials including the following components: Each component is measured by weight: The crude carbon dots are prepared from organic acid and fatty amine.

2. The low rolling resistance rubber nanocomposite material according to claim 1, characterized in that: Each component is measured by weight:

3. The low rolling resistance rubber nanocomposite material according to claim 1, characterized in that: The rubber is a bio-based rubber and / or a petroleum-based rubber; preferably one or more of natural rubber, epoxidized natural rubber, itaconate rubber, styrene-butadiene rubber, nitrile rubber and butadiene rubber; more preferably one or more of natural rubber, epoxidized natural rubber and itaconate rubber.

4. The low rolling resistance rubber nanocomposite material according to claim 1, characterized in that: The organic acid is at least one of citric acid, malic acid, oxalic acid, lactic acid, acetic acid and tartaric acid; preferably citric acid and / or malic acid; or / and, The fatty amine is at least one of ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine and polyethylenepolyamines; preferably diethylenetriamine and / or triethylenetetramine.

5. The low rolling resistance rubber nanocomposite material according to claim 1, characterized in that: The molar ratio of the organic acid to the fatty amine is 1:1-5, preferably 1:2-3.

6. The low rolling resistance rubber nanocomposite material according to claim 1, characterized in that: The weight ratio of the coarse carbon dots to white carbon black is 1:3-30, preferably 1:3-7.

7. The low rolling resistance rubber nanocomposite material according to claim 1, characterized in that: The raw materials of the rubber nanocomposite material also include maleic anhydride-added polybutadiene; based on 100 parts by weight of rubber, the weight of the maleic anhydride-added polybutadiene is 1 to 10 parts, preferably 5 to 10 parts.

8. A method for preparing the low rolling resistance rubber nanocomposite material according to any one of claims 1 to 7, characterized in that: The method comprises mixing the crude carbon dots with deionized water and then kneading the mixture with the remaining components in the amounts to obtain the rubber nanocomposite material.

9. A vulcanized rubber, characterized in that: The low rolling resistance rubber nanocomposite material is made by compression vulcanization at 120-180°C as claimed in any one of claims 1 to 7.

10. Use of the low rolling resistance rubber nanocomposite material according to any one of claims 1 to 7 in a tire.

Citation Information

Patent Citations

  • Itaconate / butadiene copolymer type bioengineering rubber and preparation method thereof

    CN104945817A

  • A bioengineered rubber of itaconic acid ester / butadiene copolymer and its preparation method

    CN104945817B

  • Preparation method of carbon dot having high fluorescent quantum yield

    CN103045242A

  • Silicon dioxide modified carbon dot fluorescent powder and fluorescent silicone rubber

    CN107663279A

  • Carbon quantum dot / rubber composite material and preparation method thereof

    CN113105676A